Solution-Generated Collapse (SGC) Structures Associated with Bedded Evaporites: Significance to base-metal and hydro-carbon localization - Simpson, F. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1988)
Summary Localized solution removal of bedded salt ofthe cratonic interior has given rise to characteristic collapse structures in the overlying strata. Solution-generated collapse (SGC) structures comprise (1) fault-bounded subsidence troughs, (2) anomalous thickness increases of lithostratigraphic units, (3) collapse breccias resting on solution residues, and (4) local absence or thickness reduction of an evaporite unit at depth. SGC structures are potential conduits for cross-formational flow of fluids (ground water and hydrocarbons) and may have served as free-ways of easy migration for brines enriched in base metals. Reconstruction of the hydro-geologic environments and ground-water regimes has potential as a strategy for location of commercial accumulations of hydro-carbons and base metals.